Review and Development Trend of the Research on Unpowered Lower Extremity Exoskeleton Robot - Kai Zheng; Lili Liu; Yongfeng Wang; Guoru Zhao (Jixie chuandong)
The unpowered lower extremity exoskeleton robot can be used in medical rehabilitation， sports assistance， load operation and other scenes.The development background and the forms of assistance of unpowered lower extremity exoskeleton robot are systematically expounded. The research history of unpowered lower extremity exoskeleton robots at home and abroad is summarized， it is classified according to multi joint and single joint， and the structure， characteristics， advantages and disadvantages， and efficiency evaluation of the two types of robots are summarized. According to the key technologies and future development trend of unpowered lower extremity exoskeleton robots， the analysis and prospect are carried out.